2003
DOI: 10.2355/isijinternational.43.555
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Dependence of Tensile Behavior and Environmental Effect in Zirconia Ceramics

Abstract: The tensile strength of four kinds of zirconia ceramics (two kinds of Y-TZP with different grain sizes, Mg-PSZ and Ce-TZP) has been investigated for a wide range of strain rates (3ϫ10 Ϫ9 -1.0ϫ10 Ϫ1 s Ϫ1) in both air and vacuum. The obviously unique strain rate dependence was observed in Y-TZPs and Mg-PSZ, which have anelastic properties. On the other hand, such strain rate dependence was not observed over the whole range of strain rates for Ce-TZP, which does not exhibit anelasticity. For all of the samples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This type of behaviour is well known in crystalline solids [15,16] and has been reported to be significant in tetragonal zirconia polycrystals (TZP) [17][18][19][20]. Due to the high temperatures, however, the viscosity parameter can be expected to be quite high.…”
Section: Anelastic Expansionmentioning
confidence: 96%
“…This type of behaviour is well known in crystalline solids [15,16] and has been reported to be significant in tetragonal zirconia polycrystals (TZP) [17][18][19][20]. Due to the high temperatures, however, the viscosity parameter can be expected to be quite high.…”
Section: Anelastic Expansionmentioning
confidence: 96%
“…Later, oxygen vacancies were proposed as a reason for anelasticity. 24,27,28 The latter theory is supported by the observed differences in the anelasticity of Y-TZP and Ce-TZP springs. If stabilizing ions with a valence different from that of Zr 4+ are incorporated into the zirconia lattice, as is the case in Y-stabilized TZP materials by incorporating Y 3+ ions, oxygen vacancies are created to maintain electroneutrality.…”
Section: Mechanism Of Anelastic Deformation Of Tzpmentioning
confidence: 76%
“…An anelastic behavior on 3Y-TZP was first demonstrated in the literature by Pan and Horibe [21][22][23] using strain gauges on flexural specimens. In a multitude of further experiments with similar experimental setup, the influence of stress intensity, deformation rate, and loading mode on the anelastic behavior of various TZP and PSZ materials was investigated by Matsuzawa and other scientists at Waseda University in Tokyo [24][25][26][27][28][29][30] in the following years. It was found that the anelastic characteristic affects phase transformation, crack growth, and ultimately the mechanical properties of TZP ceramics.…”
Section: Nonelastic Behavior Of Tzp-containing Springsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all these previous studies were limited on doped-zirconia, such as yttria-stabilized zirconia (YSZ) and ceria-stabilized zirconia (CSZ). [27][28][29] To our knowledge, effect of microscale shear stress on the martensitic phase transformation of nanocrystalline t-ZrO 2 has never been reported.…”
Section: Introductionmentioning
confidence: 92%